Environmental change as a driver of diversification in temporary aquatic habitats: does the genetic structure of extant fairy shrimp populations reflect historic aridification?. (17th March 2013) - Pinceel, Tom; Brendonck, Luc; Larmuseau, Maarten H. D.; Vanhove, Maarten P. M.; Timms, Brian V.; Vanschoenwinkel, Bram
Summary: Over the past 65 my, the Australian continent experienced a pronounced shift from predominantly wet, tropical, conditions to a much drier climate. Little is known, however, about the effect of this important continent‐wide event on freshwater organisms and ecosystems. Fairy shrimps (Crustacea; Anostraca) are ancient and specialist inhabitants of temporary and saline aquatic habitats that typically prevail under semiarid conditions. Therefore, they present suitable evolutionary models to study scenarios of historic environmental change and the impact of a drying climate on aquatic ecosystems in particular. Focussing on both macro‐ and micro‐evolution in the fairy shrimp genus Branchinella and using mitochondrial DNA data (16S and COI), we evaluated whether patterns of contemporary genetic variation reflect historic climate change. There is a close match between episodes of Cenozoic climate change and macro‐evolutionary diversification in Australian fairy shrimps, presumably mediated by a progressive increase in the abundance and diversity of temporary aquatic habitats on the continent. Micro‐evolutionary patterns reflect both range expansion and recent contraction, linked to extreme drying events during the Pleistocene glacial periods. This study effectively illustrates the potential long‐term effects of environmental change on the diversity and the evolutionary trajectories of the fauna of temporary waters. Moreover, it demonstrates the importance of adaptation to new environments and non‐adaptive processes, such as divergence in isolation, for explaining extant diversity patterns in this particular environment.